The Contribution of The Waste Bank Program to The Customer Household Income of Barokah Waste Bank in RW. 10 Sisir - Batu City - East Java - Agista Putri Setiawati; Muhammad Hasyim Ashari (CV. AFDIFAL MAJU BERKAH, 2023)
This study aims to analyze the effect of the Barokah waste bank program on community household income in the Rukun Warga (RW) 10, Sisir Village, Batu City, which is a customer of the Barokah waste bank, as well as examine the contribution of the Barokah waste bank to whether there is a change in customer household income. the Barokah waste bank before and after the existence of the Barokah waste bank. This research is a survey research using a quantitative approach, using primary data in the form of questionnaires from respondents, namely Barokah waste bank customers, totaling 118 people/person, with a sample set of 25%, namely 30 respondents using simple random sampling method. The results showed that there was no effect of the Waster Bank Program on Household Income of Barokah Waste Bank customers due to the lack of integration of the Waste Bank program with community training to produce handicraft products made from waste waste that have economic value. Meanwhile, the contribution of the existence of the Barokah waste bank shows that there is a change in household income from customers of the Barokah waste bank before and after becoming customers of the Barokah waste bank.